2014
DOI: 10.3109/21681805.2014.886289
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different scoring systems for outcome prediction in patients with Fournier's gangrene: Experience with 50 patients

Abstract: Only the UFGSI score could predict the disease severity and the patients' survival. The findings did not support previous findings that an UFGSI threshold of 9 is a predictor of mortality during initial evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 17 publications
(55 reference statements)
5
33
4
Order By: Relevance
“…This result was also confirmed by the same author's recent study. [14] In the present study, the median FGSI score was 2 (0-9) for survivors and 6 (2-14) for those who died with a significant difference between groups.…”
Section: Discussionsupporting
confidence: 40%
See 3 more Smart Citations
“…This result was also confirmed by the same author's recent study. [14] In the present study, the median FGSI score was 2 (0-9) for survivors and 6 (2-14) for those who died with a significant difference between groups.…”
Section: Discussionsupporting
confidence: 40%
“…[2,3,10,13] Some previous studies showed a younger age in survivors, although some others did not find any difference at the age of disease onset between survivors and non-survivors. [2,4,10,11,14] In our study group, there were 36 (92.3%) males, and the survivor group consisted of significantly younger patients (p=0.047). Cox regression analysis found advanced age as an independent prognostic risk factor in our study (p=0.016, 95% CI 1.017-1.176).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Delay in surgical debridement can increase the extent of the necrosis, and lead to a worse prognosis. 21,22 Early admission, rapid diagnosis, and adequate surgical treatment are crucial components in achieving a successful outcome. The median duration of symptoms before admission was a day longer in non-survivors (4 vs. 3), but this was not predictive for mortality in our study.…”
Section: Prognostic Factors Affecting Mortality In Fournier's Gangrenementioning
confidence: 99%